(3GdMQcI GdOjebQGWjI ai GdShOGf, (B1943 - 1985 /s - (3GdHMjQi, Rcis (al-Qahirah : Dar Nahdah al-Sharq, 1996)
On the modern political history of Sudan
Includes bibliographical references (p. 412-427)
Keywords: Sudan -- Politics and government -- 1956-1985; Sudan -- Politics and government -- 1985-